Design Matters: Development and Validation of the Online Course Design Elements (OCDE) Instrument - Florence Martin (Athabasca University Press, 2021)
Course design is critical to online student engagement and retention. This study focused on the development and validation of an online course design elements (OCDE) instrument with 38 Likert-type scale items in five subscales: (a) overview, (b) content presentation, (c) interaction and communication, (d) assessment and evaluation, and (e) learner support. The validation process included implementation with 222 online instructors and instructional designers in higher education. Three models were evaluated which included a one-factor model, five-factor model, and higher-order model. The five-factor and higher-order models aligned with the development of the OCDE. The frequency of use of OCDE items was rated above the mean 4.0 except for two items on collaboration and self-assessment. The overall OCDE score was related to self-reported levels of expertise but not with years of experience. The findings have implications for the use of this instrument with online instructors and instructional designers in the design of online courses.